Music composition - Jarrett, Scott; Day, Holly (--For dummies., 2024)
"Music is powerful. It can change moods, tell stories, and it can even become a lucrative career. Music Composition for Dummies introduces you to the art and craft of writing music. You'll discover how to arrange notes into chords, chords into melodies, and melodies into songs. Then, turn those songs into compositions fit for orchestras, rock bands, choirs, electronic producers, or anyone else who wants to make music. This beginner-friendly guide even shows you how to sell your compositions online. Let's go, Mozart!" --